2020
DOI: 10.1002/ajum.12225
|View full text |Cite
|
Sign up to set email alerts
|

Erector spinae plane block for multiple rib fracture done by an Emergency Physician: A case series

Abstract: The erector spinae plane block is a novel ultrasound‐guided technique that has recently been described for the management of rib fracture pain in the emergency department. This block has been used in the post‐operative period and chronic thoracic pain and is usually done by experts of anaesthesia or critical care. Erector spinae plane block is an unexplored domain for rib fracture pain management in emergency department. We highlight the use of this block is a safe and effective block that can be performed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…In this study, it was observed that there was a statistically significant reduction in the pain scores in the ESPB group up through 120 min. A similar reduction in pain was noted in a case series conducted in an ED 22 . However, they were able to follow the patient only up to 2 h postprocedure following which the patients were either shifted to wards or had to go to a different hospital.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In this study, it was observed that there was a statistically significant reduction in the pain scores in the ESPB group up through 120 min. A similar reduction in pain was noted in a case series conducted in an ED 22 . However, they were able to follow the patient only up to 2 h postprocedure following which the patients were either shifted to wards or had to go to a different hospital.…”
Section: Discussionsupporting
confidence: 60%
“…A similar reduction in pain was noted in a case series conducted in an ED. 22 However, they were able to follow the patient only up to 2 h postprocedure following which the patients were either shifted to wards or had to go to a different hospital. Another retrospective study done in a Level I trauma center found that the mean pain scores were reduced from 7.7 to 4.7 in the first 3 h postintervention.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve blocks develop into a critical component of emergency management of such injuries leading to better patient outcomes and patient satisfaction with analgesia. The Erector spinae block has already been shown to be effective in terms of analgesia for fractures of the posterior ribs and fractures of transverse processes of the vertebrae as shown by previous studies involving authors in this book [59].…”
Section: Injuries To the Chest Wall And Nerve Blocksmentioning
confidence: 54%
“…3 Bilateral ESPB has since been used in a variety of clinical cases, including as a part of multimodal analgesia following thoracic and cardiovascular surgeries, or for chronic low-back pain, vertebral fractures, acute pancreatitis, and rib fractures. [4][5][6] Risks of the procedure include pneumothorax, nerve injury, and local anesthesia toxicity. However, few complications of ESPB have been published.…”
Section: Mount Sinai Medical Center Department Of Emergency Medicine ...mentioning
confidence: 99%